Empathy and Narrative: A Discussion of Contemporary Stories from Childcare and Healthcare - Burgess, Simon; Rogers, Marg; Jeffries, Diana (International Electronic Journal of Elementary Education, 2023)
In caring professions, such as childcare and healthcare, empathy and narrative underpin important aspects of the work of early childhood educators and nurses. Unfortunately, they are not given much attention in scholarly articles. This cross-disciplinary paper discusses the virtue of empathy from a philosophical stance, and its relationship to narrative when building shared understandings. There is a sense in which empathy and narrative are interdependent: storytelling helps to cultivate empathy in others, and empathy can be essential if we are to elicit and understand the stories that others have to tell. In fact, when it comes to eliciting and understanding the kinds of stories that are of particular interest for this paper (i.e., the personal stories to be told by young children participating in a research project, and those of patients in a healthcare setting), empathy tends to be especially important. As we argue, these examples drawn from early childhood education and care and healthcare serve to illustrate certain ways in which empathy, storytelling, and the development of shared understandings can be of deep significance; not only for researchers, educators and healthcare professionals but also for senior administrative and public policy officials.